Sistem Monitoring Detak Jantung Pasien Berbasis LoRa - Sari, Indah Permata; Rahayu, Yusnita; Masdar, Huriatul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
This research developed a heart rate monitoring system using 3 lead electrodes sensor based LoRa. LoRa used to send the data from transmitter to receiver. Hardware used is arduino uno, ad8232, lora shield and electrodes. The result of patient’s heart rate monitoring are displayed on Graphical User Interface (GUI) designed in visual basic 2010. Visual basic provide information such as heart rate per minute, heart rate signal and heart rate characteristic such a bradicardia, tacycardia and normal. Based on the test result, LoRa can work better in Line of Sight (LoS) condition compared with non-LoS condition. For LoS condition, RSSI is at interval of -96 to -107 dBm for distance of 50 meters to 200 meters, while for non-LoS condition is at interval of -103 to -113 dBm. The result of patient’s heart rate monitoring show a heart rate error of 5.98 % with signal intervals that are still classified in the normal range category.Keyword: ECG, LoRa, Monitoring